The risk of pathogenic microbiological contamination of South African fresh fruit for the export and local market - Badenhorst, Adriaan Bernard (Stellenbsoch : Stellenbosch University, 2020)
Thesis (MScFoodSc)--Stellenbosch University, 2020.